2017
DOI: 10.3892/mmr.2017.7012
|View full text |Cite
|
Sign up to set email alerts
|

Elastin-derived peptides are involved in the processes of human temporomandibular disorder by inducing inflammatory responses in synovial cells

Abstract: Temporomandibular joint dysfunction (TMD) is a collection of clinical symptoms that involve masticatory muscles and the temporomandibular joint (TMJ). Common symptoms include limited jaw motion and joint sound/pain, along with TMJ disc displacement. TMD is frequently associated with synovitis, a chronic inflammation of the synovium. Fibroblast-like synovial cells have been identified to produce several inflammatory mediators and may have an important role in the progression of TMJ inflammation. Degradation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…Thermal stimuli were delivered to the forearm for 5 s while we recorded high-density EEG. The rationale for stimulating the subject's forearm rather than jaw, was to avoid potential between group differences that are focal to the jaw area in orofacial pain including lower pain thresholds in the masseter and anterior temporalis muscles (Farella et al, 2000; Hansdottir and Bakke, 2004), elevated levels of IL-6, IL-7, IL-8 and IL-13 in the masseter muscle (Louca Jounger et al, 2017), and elevated levels of elastin-derived peptides and IL-6 in the synovial fluid (Kaneyama et al, 2002; Kobayashi et al, 2017). EEG data were analyzed using time-frequency analysis, source-localization analysis, and measure projection analysis (MPA) (Bigdely-Shamlo et al, 2013), which together allowed us to characterize neuronal activity at different frequency bands in source space.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal stimuli were delivered to the forearm for 5 s while we recorded high-density EEG. The rationale for stimulating the subject's forearm rather than jaw, was to avoid potential between group differences that are focal to the jaw area in orofacial pain including lower pain thresholds in the masseter and anterior temporalis muscles (Farella et al, 2000; Hansdottir and Bakke, 2004), elevated levels of IL-6, IL-7, IL-8 and IL-13 in the masseter muscle (Louca Jounger et al, 2017), and elevated levels of elastin-derived peptides and IL-6 in the synovial fluid (Kaneyama et al, 2002; Kobayashi et al, 2017). EEG data were analyzed using time-frequency analysis, source-localization analysis, and measure projection analysis (MPA) (Bigdely-Shamlo et al, 2013), which together allowed us to characterize neuronal activity at different frequency bands in source space.…”
Section: Introductionmentioning
confidence: 99%
“…Our data show that VGVAPG peptide did not increase ROS production and induce caspase-1 activation and cell proliferation in all studied concentrations and time intervals in 3T3-L1 cell line. To date, previous studies have shown that EDPs and/or VGVAPG peptide increase the production and/or secretion inflammatory markers such as IL-1α, IL-1β, and IL-6 in ligamentum flavum cells, synovial cells, and melanoma cell lines [ 63 65 ]. On the other hand, our previous studies show that VGVAPG peptide increases the expression of PPARγ and decreases the expression of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) and production of IL-1β in mouse astrocytes in a PPARγ-dependent manner, which suggest that the effect of VGVAPG is tissue dependent [ 31 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results highlight the potential role of cytokines in TMJD pathogenesis. Our previous study showed that IL-6 expression in the synovial fluid obtained from patients with TMJD was significantly correlated with the two clinical parameters of TMJ locking and pain/jaw function based on a visual analogue scale (VAS) ( 13 ). Additionally, the concentration of elastin-digested peptides in the synovial fluid of patients with TMJD was significantly associated with the TMJ locking duration, the VAS and IL-6 expression ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study showed that IL-6 expression in the synovial fluid obtained from patients with TMJD was significantly correlated with the two clinical parameters of TMJ locking and pain/jaw function based on a visual analogue scale (VAS) ( 13 ). Additionally, the concentration of elastin-digested peptides in the synovial fluid of patients with TMJD was significantly associated with the TMJ locking duration, the VAS and IL-6 expression ( 13 ). In vitro , elastin-digested peptides act on human TMJ synovial cells to promote IL-6 upregulation and MMP-12 (an elastin-degrading enzyme) ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation